Facilitating the Creative Process Through Collaboration - Jennifer K. Fortuna (Scholarworks @ WMU, 2019)
Miles Parker Scharfenberg, an artist based in Richland, Michigan, provided the cover art for the Fall 2019 edition of The Open Journal of Occupational Therapy (OJOT). "Late Night Fireworks" is a 30" x 40" painting made from acrylic on canvas. Born 15 weeks premature, Miles' multiple health impairments have made it difficult to engage in meaningful occupations, such as painting. With support from his mother, Carol; occupational therapy students; and members of the community; Miles creates colorful abstract expressionist paintings. Collaboration is part of his creative process. In this fifth anniversary issue of OJOT, Occupation and the Artist is following up with a past artist for the first time. Over the last five years, Miles has further developed his skill and abilities as a painter while discovering his potential as an artist.